Popliteal vein thrombosis associated with femoral osteochondroma and popliteal artery pseudoaneurysm. - Scott, E. M. (BMJ Group, 1995)
Deep vein thrombosis is a common condition thought to be caused by impaired venous blood flow or hypercoagulable blood states. However, often no predisposing cause can be found. We describe a deep vein thrombosis formed in association with femoral osteochondroma and popliteal artery pseudoaneurysm. It is an interesting combination that has only been described once before.